MAP1B mutations cause intellectual disability and extensive white matter deficit - G. Bragi Walters (Nature Portfolio, 2018)
Intellectual disability (ID) is characterized by an intelligence quotient of below 70 and impaired adaptive skills. Here, analyzing whole genome sequences from 31,463 Icelanders, Walters et al. identify variants in MAP1B associated with ID and extensive brain-wide white matter deficits.